THE IMPACT OF QUALITY OF WORK LIFE (QWL) AND KNOWLEDGE MANAGEMENT ON EMPLOYEE PERFORMANCE AT PT HUTAHAEAN DALU-DALU - Sihombing, Nisya Margaretha; Eriza, Faisal; Siregar, Onan Marakali (Simangunsong : Journal of Business Administration, Management, Economic And Accounting, 2023)
This study aims to analyze the impact of quality of work life (qwl) and knowledge management partially on the performance of PT Hutahaean Dalu-Dalu employees. Then to analyze the impact of quality of work life (qwl) and knowledge management simultaneously on the performance of PT Hutahaean Dalu- Dalu employees. This study uses quantitative methods involving 70 employees of PT Hutahaean Dalu- Dalu as research samples. The sampling technique is purposive sampling and proportionate stratified random sampling. The data collection used is a questionnaire using a Likert scale. The data analysis technique used instrument test of reliability validity, classical assumption test and hypothesis test using multiple linear regression analysis using SPSS. The results of this study indicate that the quality of work life (qwl) has no significant impact on the performance of PT Hutahaean Dalu-Dalu employees. Meanwhile, knowledge management has significant impact on the performance of PT Hutahaean Dalu- Dalu employees. Simultaneously quality of work life (qwl) and knowledge management impact the performance of PT Hutahaean Dalu-Dalu employees and are able to affect employee performance by 40%, the remaining 60% is explained by other variables or factors.